Studi Pendahuluan Perspektif Guru terhadap Literasi Sains dan Pemahaman Konsep dalam Pembelajaran Biologi SMA - Mote, Elsa Merinda Isabela; Magdalena, Marini; Ainulhaq, Nurisa (Jurnal Pendidikan Tambusai, 2026)
Science literacy is essential for understanding biology concepts in high school, yet its integration within the Merdeka Curriculum remains limited due to low reading interest and student misconceptions. This study aims to analyze science literacy conditions and conceptual understanding based on biology teachers' perceptions. Employing a descriptive qualitative approach, research was conducted at SMAN 8 Kota Serang with one grade X biology teacher as the sample. Semi-structured interview guidelines served as the instrument, analyzed through data reduction, presentation, and conclusion drawing. Findings reveal partial science literacy integration through discussions, but conceptual understanding varies due to limited data interpretation skills and complex terminology. Teachers emphasize the need for systematic science literacy assessment. This preliminary study justifies the need for subsequent quantitative research.